(untitled) (diségno, 2021)
First, I would like to express my contentment that the theme chosen for the conference consists of a verb related to the action of Disegno. For me, Disegno, in any of its forms, is an action, a practice consubstantial with a thought whose end, as an instrument of its expression, is (etymologically) always entirely involved. Indeed, I maintain that any authentic reflection on Disegno cannot overlook considerations specifically reserved for the modes of action; it therefore cannot but help to contribute to building a theory of its practice... (read more)